PENGUKURAN TINGKAT KEPUASAN DOSEN DAN MAHASISWA DALAM PROSES PEMBELAJARAN E-LEARNING PADA UNIVERSITAS BUNDA MULIA - Leli Deswindi (Business Management Journal, 2017)
The level of competition among universities in Indonesia is in a very competitive one. Each univesity tries to attract new student to choose which university to continue their educational program. This level of competition makes all universities in Indonesia promote themselves and try to develop program and facilities as well as possible. Bunda Mulia University (BMU) has taken a very smart strategy to anticipate this competition by providing E-leaning (Electronic Learning) program or it is better known BM-learning (Bunda Mulia learning). They are many components involved in this program. The most important components of e-learning program are the system, lecturers and students. To increase E-learning facilities, BMU need to put lecturers and students satisfaction on the first priority. In this research, the writer tries to find out the level of satisfaction from lecturers and students who have been involved in e-learning program. The result of this research could be use as an input for the management of Bunda Mulia University.Keywords : satisfaction level, lecturers & students, e-learning